Prevalence of Aflatoxin B1 and B2 in Poultary Feed (Nepal Agriculture Research Journal, 2014)
A total of 65 poultry feed samples were examined for the detection of aflatoxin (aflatoxin B1 and aflatoxin B2) using thin layer chromatography (TLC). Samples were collected from Chitwan and Kavrepalanchock districts. Out of those samples examined a total of 49 (75.38%) samples were found positive. Out of 49 (75.38%) samples positive, 42 (85.71%) samples were found positive both with aflatoxin B1 and B2 where as five (10.20%) samples were positive only with aflatoxin B1 and two (4.08%) samples were positive only with aflatoxin B2. Among them 13 (20%) samples were found positive having aflatoxin above permissible level. The concentration of aflatoxin in positive samples ranged from trace to 366 ppb (366 μg/kg). Likewise, out of 52 samples examined in rainy season, 40 samples (76.92%) were found positive where as out of 13 samples examined in winter season 9 (69.23%) were found positive.Nepal Agric. Res. J. Vol. 9, 2009, pp. 109-112DOI: http://dx.doi.org/10.3126/narj.v9i0.11648